2016
DOI: 10.1002/dc.23476
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical utility of claudin‐4 versus those of Ber‐EP4 and MOC‐31 in effusion cytology

Abstract: Since CL4 exhibited similar or superior usefulness to Ber-EP4 and MOC-31, it could become the first choice for the above differential diagnosis in effusion cytology. Diagn. Cytopathol. 2016;44:499-504. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 19 publications
(21 reference statements)
2
31
0
Order By: Relevance
“…Claudin 4 shows improved sensitivity and specificity over Ber-EP4 and MOC-31 for distinguishing adenocarcinoma from cells of mesothelial origin. [13][14][15] Although Ber-EP4 and MOC-31 are reasonably sensitive as adenocarcinoma markers, both demonstrate positive staining in a subset of epithelioid mesotheliomas, which represents a potential diagnostic pitfall in effusion specimens. 14,15 A study found no membranous staining in 75 malignant mesotheliomas, although 11% (8 of 75 cases) had weak cytoplasmic staining, which is considered nonspecific.…”
Section: Claudinmentioning
confidence: 99%
“…Claudin 4 shows improved sensitivity and specificity over Ber-EP4 and MOC-31 for distinguishing adenocarcinoma from cells of mesothelial origin. [13][14][15] Although Ber-EP4 and MOC-31 are reasonably sensitive as adenocarcinoma markers, both demonstrate positive staining in a subset of epithelioid mesotheliomas, which represents a potential diagnostic pitfall in effusion specimens. 14,15 A study found no membranous staining in 75 malignant mesotheliomas, although 11% (8 of 75 cases) had weak cytoplasmic staining, which is considered nonspecific.…”
Section: Claudinmentioning
confidence: 99%
“…Immunostains that can distinguish between mesothelial, both reactive or neoplastic, and epithelial cells in effusions continue to be evaluated in human pathology . Such a comprehensive evaluation has never been performed in the veterinary field, although its importance is well recognized .…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity for metastatic carcinoma detection from effusion/peritoneal washing was 100, 97.64 and 88.23% for claudin-4, MOC-31 and p16, respectively. Claudin-4 was used as a reference for comparison with the p16 results since it is considered as the most sensitive marker to distinguish adenocarcinomas from reactive and malignant mesothelial cells in cytology of effusions [18,19]. MOC-31 is also a useful diagnostic marker with high sensitivity and specificity for differentiating malignant from benign effusions.…”
Section: Discussionmentioning
confidence: 99%
“…MOC-31 is also a useful diagnostic marker with high sensitivity and specificity for differentiating malignant from benign effusions. However, this marker may not be expressed in some carcinomas of histological types other than adenocarcinomas, which may result in false negative diagnoses [18].…”
Section: Discussionmentioning
confidence: 99%